Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2021)
A dataset containing 10204247 species occurrences available in GBIF matching the query: { "and" : [ "OccurrenceStatus is Present", "TaxonKey is Fagales" ] } The dataset includes 10204247 records from 2709 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0084641-210914110416597/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences